"I just hope the whole thing won't collapse": "understanding" and "overcoming" the EU financial crisis from the citizens' perspective - Andreas Hepp; Swantje Lingenberg; Monika Elsler; Johanna Möller; Anne Mollen; Anke Offerhaus (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2013)
Based on qualitative research conducted in Austria, Denmark, France, Germany, Poland, and the United Kingdom, the article analyses the citizens' perspective on the EU financial crisis as it is communicated in the European public sphere. With reference to this aim, we argue in the following steps: After a general introduction into the research field we describe our overall theoretical approach on the citizens' role in the process of a communicative construction of the European public sphere. The following section introduces the methodological approach, triangulating qualitative interviews, a half-standardised questionnaire, qualitative network maps and media diaries. We go on to present our research results on the citizens' constructions of the EU financial crisis. On the one hand, they are struggling to understand the crisis, a process that is marked by perplexity, anxiety, and speculations. On the other hand, the citizens develop their own view on how to overcome the crisis, either in a national way, a European way, or by re-negotiating European cooperation. Based on such an analysis we conclude by a general reflection whether the crisis is a problem for the EU and its public sphere. – – Das Ziel des Artikels ist es, basierend auf qualitativer Forschung in Dänemark, Deutschland, Frankreich, Großbritannien, Österreich und Polen die Sicht der Bürgerinnen und Bürger auf die in der europäischen Öffentlichkeit kommunizierte EU-Finanzkrise zu rekonstruieren. Bezug nehmend auf dieses Ziel argumentieren wir wie folgt: Nach einer allgemeinen Einleitung in das Forschungsfeld legen wir unseren theoretischen Ansatz zur Rolle der Bürgerinnen und Bürger im Prozess der kommunikativen Konstruktion einer europäischen Öffentlichkeit dar. Hierauf folgend wird der empirische Ansatz unserer Forschung vorgestellt, die qualitative Interviews, habstandardisierte Befragung, qualitative Netzwerkforschung und Medientagebücher trianguliert. Im Anschluss werden die von uns herausgearbeiteten Konstruktionen der EU Finanzkrise dargelegt. Auf der einen Seite bemühen sich die Interviewten, die Krise zu verstehen, wobei Ratlosigkeit, Sorgen und Spekulationen dominieren. Auf der anderen Seite entwickeln die Bürgerinnen und Bürger ihre eigene Sicht darauf, wie die Krise zu überwinden ist. Hierbei fallen unterschiedliche Vorstellungen von nationalen Wegen, europäischen Wegen und dem Neuverhandeln der europäischen Zusammenarbeit auf. Basierend auf dieser Analyse ziehen wir am Ende des Beitrags ein allgemeines Fazit im Hinblick auf die Frage, inwieweit die EU Finanzkrise ein Problem für die EU und deren Öffentlichkeit darstellt.
Keywords: 300